Advanced Topical Carriers of Butenafine HCL for Effective Fungal Therapy - SIDDHI SANTOSH GAVALI; PALLAVI SINGH CHOUHAN (International Journal of Pharmacy and Pharmaceutical Sciences, 2026)
Superficial fungal infections are common dermatological conditions worldwide, frequently requiring sustained treatment and susceptible to recurrence. Conventional topical therapies often face challenges such as poor skin penetration, inadequate drug retention, and limited therapeutic effectiveness at the infection site. BUTE HCl an effective antifungal agent, shows potential for treating superficial fungal infections; however, its therapeutic performance is limited due to poor aqueous solubility and restricted skin permeation. Therefore, advanced formulation approaches are required to enhance its topical delivery. A literature search was performed using databases including PubMed, Scopus, and SciFinder. The search was conducted using keyword such as “Butenafine hydrochloride”, “topical antifungal delivery”, “nanocarriers”, “lipid-based systems”, and “nanoformulations”. Studies related to topical delivery approaches, formulation development, and evaluation of BUTE HCl were included. Recent advancements in nanotechnology have increased interest in the development of novel BUTE HCl delivery systems, including lipid–based nanoparticles, nanoemulsions, nanomicelles, and other nanocarriers. These systems have demonstrated improved formulation characteristics, enhanced skin permeation, prolonged retention, and controlled drug release. Nanocarriers-based approaches improve the solubility and topical performance of BUTE HCl, thereby enhancing antifungal effectivenss. Nanotechnology-based topical formulations provide promising strategies for improving BUTE HCl delivery by enhancing skin retention, increasing drug availability at the infection site, and providing sustained release. Further studies focusing on clinical evaluation, large–scale manufacturing, stability assessment, and regulatory approval are required for successful translation into pharmaceutical applications.